Dual-Edged Character of Quorum Sensing Signaling Molecules in Microbial Extracellular Electron Transfer - Yang, Yang; Zhou, Huihui; Mei, Xiaoxue; Liu, Bingfeng; Xing, Defeng (Frontiers in Microbiology, 2018)
Quorum sensing (QS) is a central mechanism for regulating bacterial social networks in biofilm via the production of diffusible signal molecules (autoinducers). In this work, we assess the contribution of quorum sensing autoinducers to microbial extracellular electron transfer (EET) by Pseudomonas aeruginosa strain PAO1 and three mutants pure culture-inoculated in microbial electrolysis cells (MECs) and microbial fuel cells (MFCs). MECs inoculated with different P. aeruginosa strains showed a difference in current generation. All MFCs reached a reproducible cycle of current generation, and PQS-deficient pqsA mutant inoculated-MFCs obtained a much higher current generation than pqsL mutant inoculated-MFCs which overproduced PQS. lasIrhlI-inoculated MFCs produced a lower power output than others, as the strain was deficient in rhl and las. Exogenous N-butanoyl-l-homoserine lactone could remedy the electricity production by lasIrhlI mutants to a level similar to wild-type strains while signaling molecules had little effect on wild-type bacteria in MFCs. Meanwhile, experiments with the wild-type and pqsA, pqsL mutants indicated that the overexpression of PQS signaling molecules made no significant contribution to EET. QS signaling molecules therefore have dual-edged effects on microbial EET. These findings will provide favorable suggestions on the regulation of EET, but detailed QS regulatory mechanisms for extracellular electron transfer in pure- and mixed-cultures are yet to be elucidated.